Does Inclusion Guarantee Institutional Autonomy? The Case of the Inter-American Development Bank - Diego Hernandez (University of Heidelberg, Department of Economics, 2013)
Discontent with the substantial influence of major global players in International Financial Institutions (IFIs) has raised a call to restructure these organizations. Greater involvement of borrowing members in lending decisions has been proposed in order to limit the exposure of development resources to the interests of large donors. No consensus has been reached, however, if such eventual reforms would create more independent and efficient IFIs. Through its analysis of the allocation patterns of the Inter-American Development Bank (IDB), this paper contributes to the debate on whether greater representation of borrowers in the governance of IFIs truly translates into fairer lending practices. Far from being a fully democratic institution, the IDB is nevertheless an example of a major IFI not dominated by non-borrowers, and its organization and lending behavior may well provide some clues to resolve the broader debate. Empirical results from examining IDB loan commitments granted during the 1970-2007 period reveal that control over IDB allocation decisions by its largest stakeholder, the US, is limited. This atypical finding is a result of the strong influence of borrowing members in the governance of the Bank. In particular, interest heterogeneity among the US and large borrowers leads to distributional conflicts, thereby creating the opportunity for greater institutional autonomy.
urn:nbn:de:bsz:16-heidok-146981
Keywords: 330; Inter-American Development Bank; United States; Governance; Aid Allocation